2009
DOI: 10.3341/kjo.2009.23.2.65
|View full text |Cite
|
Sign up to set email alerts
|

Dry Eye After Cataract Surgery and Associated Intraoperative Risk Factors

Abstract: PurposeTo investigate changes in dry eye symptoms and diagnostic test values after cataract surgery and to address factors that might influence those symptoms and test results.MethodsTwenty-eight eyes from 14 patients with preoperative dry eye (dry eye group) and 70 eyes from 35 patients without preoperative dry eye (non-dry eye group) were studied prospectively. In each group, we measured values such as tear break-up time (tBUT), Schirmer I test (ST-I), tear meniscus height (TMH), and subjective dry eye sympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
178
1
47

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 229 publications
(234 citation statements)
references
References 21 publications
8
178
1
47
Order By: Relevance
“…Most surgical procedures, especially surgical incisions that cause denervation of the cornea, also result in impaired epithelial wound healing, increased epithelial permeability, decreased epithelial metabolic activity and loss of cytoskeletal structures associated with cellular adhesion [5]. The changes in tBUT and Schirmer tests have been reported in previous studies [1,2,4,[9][10][11]. In our study, compared with before surgery, tBUT was markedly decreased at 3 days and slightly improved up to 3 months, but it was still lower than baseline at 3 months.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Most surgical procedures, especially surgical incisions that cause denervation of the cornea, also result in impaired epithelial wound healing, increased epithelial permeability, decreased epithelial metabolic activity and loss of cytoskeletal structures associated with cellular adhesion [5]. The changes in tBUT and Schirmer tests have been reported in previous studies [1,2,4,[9][10][11]. In our study, compared with before surgery, tBUT was markedly decreased at 3 days and slightly improved up to 3 months, but it was still lower than baseline at 3 months.…”
Section: Discussionmentioning
confidence: 98%
“…Despite microincision size which causes less damage to corneal nerves than large incision, increase of dry eye-associated symptoms and signs have indicated that the incision size is not the only mechanism of aggravation of dry eye-associated symptoms. The mechanism for the exacerbation of ocular surface damage likely includes several factors: increased inflammatory mediators due to postoperative inflammation, misuse of eye drops, toxicity from the use of benzalkonium chloride containing eye drops, decrease in corneal sensitivity which is resulted in reduced tear production, and exposure to light from the operating microscope [1][2][3][4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this investigation, the iris was removed in the case of iris adhesions, and multiple sphincterotomy was used to enlarge the visible pupillary area, increasing visual acuity [13]. Some studies suggest that cataract surgery may aggravate existing corneal diseases, including inflammation, infection and dry eye [21,22]. Therefore, it is important to identify existing corneal diseases and exclude activity eye infection before performing this procedure.…”
Section: Discussionmentioning
confidence: 99%
“…After cataract surgery many patients complain of foreign body sensation, irritation, redness and blurring of vision which are considered as unwanted effects of the surgery. 8 These effects are worse in the elderly population and in some cases may persist and develop into a full fledged dry eye syndrome requiring treatment. Thus, inspite of a perfect cataract surgery and a good snellen's visual acuity the patients may remain dissatisfied.…”
Section: Introductionmentioning
confidence: 99%